2015
DOI: 10.1016/j.ijpharm.2015.09.063
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the influence of drug–polymer interactions on the miscibility, processability and structure of polyvinylpyrrolidone-based hot melt extrusion formulations

Abstract: While hot melt extrusion is now established within the pharmaceutical industry, the prediction of miscibility, processability and structural stability remains a pertinent issue, including the issue of whether molecular interaction is necessary for suitable performance. Here we integrate the use of theoretical and experimental drug-polymer interaction assessment with determination of processability and structure of dispersions in two polyvinylpyrrolidone-based polymers (PVP and PVP vinyl acetate, PVPVA). Caffei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Similarly, the aged extrudates showed no drug melting event, indicating the absence of drug recrystallization after aging. Similar results were reported in the literature using paracetamol; however, upon extrusion temperatures above 120 °C [ 38 ].…”
Section: Resultssupporting
confidence: 90%
“…Similarly, the aged extrudates showed no drug melting event, indicating the absence of drug recrystallization after aging. Similar results were reported in the literature using paracetamol; however, upon extrusion temperatures above 120 °C [ 38 ].…”
Section: Resultssupporting
confidence: 90%
“…drug-polymer system. Several research articles used this decrease of the melting temperature as an indicator of solid dosage forms polymer miscibility [59,60]. Mixing HPMC with PEG reduced the melting temperature of PEG from 24.7 to 6.3 • C (i.e.…”
Section: Mcc-pegmentioning
confidence: 99%
“…Fule et al [55] reported the feasibility of industrially manufacturing co-formulated extrudates using two model drugs in hydrophilic polymeric matrices. The use of theoretical and experimental drug-polymer interaction assessment with determination of processability and structures of dispersions in two polyvinylpyrrolidone-based polymers (PVP and PVP vinyl acetate, PVPVA) was highlighted by Chan et al [56]. Dong et al [57] reported a novel in situ synchrotron wide-angle X-ray diffraction (WAXD)-based approach to rapidly and accurately screen the formation of cocrystal and/or salts during heating inside an extruder barrel.…”
Section: Applications Via Hmementioning
confidence: 99%